Trypanosoma Cruzi intradomiciliary transmission by Rhodnius ecuadoriensis - Fernández Ronquillo, Telmo (Revista Universidad de Guayaquil, 2010)
The present research technique was developed makes in the Sugar Cane research Center of Ecuador (CINCAE), and in the San Carlos, Valdez and Ecudos Sugar Mills, between January and December of 2007. Its main goals were: 1) To determine the biology of Aprostocetus sp; 2) To determine the para- sitic predatory capacity of Aprostocetus sp. over eggs of Perkinsiella saccharicida; 3) To evaluate the parasitic and predatory capacity of Aprostocetus sp. in field conditions; and 4) To determine the effect of the Malathion insecticide application on the parasitic and predatory activity of Apros- tocetus sp. Aprostocetus has a complete or holometabolous metamorphosis, reproduction is sexual and parthenogenic. The time from the parasitization until adult emergence was 21 ± 3.0 days. The average adult longevity was 6 ± 6 days, ranging from 1 to 22 days. The highest percentage of para- sitism and priority of Aprostocetus was registered on leaves TVD+ 4and TVD+5. Levels of parasitism and priority in the three mills were very variable levels reaching 28.1% in the mill Valdez December. Moreover, the record was more than rotten eggs parasitized eggs. The correlation analysis showed a greater association between the parasitic activity of Aprostocetus sp and abiotic factors tempera- ture and precipitation. The application of Malathion insecticide significantly affected the parasitic activity of Aprostocetus until 45 days after application.